Perbandingan Advaita Vedanta, Dvaita, dan Vishishtadvaita dalam Pendidikan Filsafat Agama Hindu - Pranatha, I Putu Eryn (Civiliza Publishing, Indonesia., 2024)
This article aims to compare the Advaita Vedanta, Dvaita, and Vishishtadvaita schools of thought within the context of Hindu religious philosophy. As one of the oldest religions, Hinduism encompasses a rich and complex philosophical heritage, with an important aspect being the understanding of the divine nature. This study investigates the history and background of these three schools, their underlying principles, key figures, and significant works. By comparing these perspectives, the article addresses the research question: How do the views of Brahman in Advaita Vedanta, Dvaita, and Vishishtadvaita differ and resemble each other, and how do these similarities and differences influence Hindu religious teachings overall? To answer this question, the article will refer to primary and secondary sources, including classic Hindu texts such as the Upanishads, Bhagavad Gita, and Brahma Sutra, as well as works by renowned Hindu philosophers like Adi Shankaracharya, Ramanuja, and Madhva. Additionally, the paper examines recent academic research on Hindu religious philosophy to provide a comprehensive and accessible analysis of the topic.